2015
DOI: 10.1111/andr.12037
|View full text |Cite
|
Sign up to set email alerts
|

Testicular histomorphometry and the proliferative and apoptotic activities of the seminiferous epithelium in Syrian hamster (Mesocricetus auratus) during regression owing to short photoperiod

Abstract: SUMMARYDuring the non-breeding season some animals exhibit testicular atrophy, decreased testicular weight and reduced seminiferous tubule diameter accompanied by depletion of the seminiferous epithelium. Some cellular factors involved in this depletion are changes in germ cell proliferation and apoptosis. In the Syrian hamster this depletion has been studied histologically and in terms of the involvement of proliferation and apoptosis in the seminiferous epithelium of fully regressed testes. The objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 68 publications
7
44
0
Order By: Relevance
“…We observed testicular b-endorphin expression in P. obesus in long photoperiod while in Syrian hamster Mesocricetus auratus [27], the level of POMC [28] and the b-endorphin immunoreactivity [28] were strong in short photoperiod. These data suggest that b-endorphin can play an important role in the regulation of seasonal gonadal activity depending on the species reproductive cycle.…”
Section: Discussionmentioning
confidence: 69%
“…We observed testicular b-endorphin expression in P. obesus in long photoperiod while in Syrian hamster Mesocricetus auratus [27], the level of POMC [28] and the b-endorphin immunoreactivity [28] were strong in short photoperiod. These data suggest that b-endorphin can play an important role in the regulation of seasonal gonadal activity depending on the species reproductive cycle.…”
Section: Discussionmentioning
confidence: 69%
“…However, conclusive data in the Syrian hamster was only recently provided by Seco-Rovira et al [2014] showing that apoptotic incidence peaks during the period of testis regression and not later when the process has been completed, and the increase is high enough to explain a massive depletion of the germinative epithelium. The same authors also showed that apoptotic germ cells are phagocytized by Sertoli cells [Seco-Rovira et al, 2015]. An inverse rela- tionship between germ cell proliferation and apoptosis has been found during seasonal testicular changes in roe deer [Blottner et al, 1995[Blottner et al, , 1996Schön et al, 2004].…”
Section: Cellular Mechanisms Of Testis Regression In Vertebrates: Thementioning
confidence: 99%
“…As a consequence of this reduction in gonadotropins, the testis atrophies or undergoes regression. In the case of the Syrian hamster ( Mesocricetus auratus ), testicular regression involves decreased testicular weight and volume and lower rates of androgen synthesis and spermatogenesis (Berndtson & Desjardins, ; Seco‐Rovira et al, ). This loss in spermatogenesis involves a depletion of the seminiferous epithelium with the arrest of spermatogenesis in primary spermatocytes (Hikim, Bartke, & Russell, ).…”
Section: Introductionmentioning
confidence: 99%
“…For other authors, the cause of reduced sperm formation in the nonbreeding season is the reduction in spermatogonia proliferation (Roelants, Schneider, Göritz, Streich, & Blottner, ). Recent studies in the Syrian hamster indicate that increased germ cell and Sertoli cell apoptosis, decreased spermatogonial proliferation and the phagocytosis of late spermatids would be the major causes of depletion of the seminiferous epithelium in the regression following a short photoperiod (Seco‐Rovira et al, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation